Acceptance and Use of the Integrated Service Information System (Silangit) at the Tegal Fisheries Training and Extension Center: The Utaut and Delone-McClean Approaches - Alfiana Nur Aisyah; Mohammad Riza Sutjipto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The implementation of the Integrated Fisheries Services Information System (SILANGIT) at the Tegal Fisheries Training and Extension Center (BPPP) aims to promote the digitization of fisheries training and certification registration. However, users’ utilization of the system has not yet been optimal and continues to face technical and operational challenges. This study aims to analyze the factors influencing Behavioral Intention and Actual Use Behavior of the SILANGIT application by integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) framework and the DeLone & McLean Information Systems Success Model. This quantitative study employed Partial Least Squares-based Structural Equation Modeling (PLS-SEM) using SmartPLS. The sample comprised 386 respondents selected via Proportional Stratified Random Sampling based on the Slovin formula and statistical power thresholds. The results of the hypothesis testing indicate that all direct hypotheses have a positive and significant effect ( ). Social Influence is the most dominant predictor of Behavioral Intention, followed by Effort Expectancy, Information Quality, System Quality, and Performance Expectancy. These five variables collectively explain the variance in Behavioral Intention. Furthermore, Behavioral Intention and Facilitating Conditions were found to have a strong direct effect on Use Behavior. Through Priority Index analysis, active feature exploration was identified as the primary operational gap. The practical implications of this study recommend improving the PTSP Helpdesk services, optimizing the application to make it lighter and more data-efficient, and conducting edutainment-based outreach to encourage optimal and sustainable system usage.